Interactive Documentary and Data Visualization: New Approaches to Telling Stories with Data - López-Lozano, Andrea; Herrero-Solana, Víctor; Sánchez-Mesa Martínez, Domingo (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2024)
Software development has influenced cultural products for years, and documentaries have not been an exception in this revolution. From non-linear and interactive webdocs to participatory, co-created, and transmedia projects, the documen-tary genre has given rise to diverse narrative structures. We analyze how webdocs have devel-oped different strategies when integrating data visualization into their narratives and interfaces. Multimedia content and data visualizations have been gaining prominence over film, and projects that don't use video have been considered docu-mentaries. This has given rise to what we consider the germ of a new genre and a new set of narrative structures.